Rancang Bangun Monitoring Sumber Energi Listrik pada Kapal Berbasis IoT - Tenokto Nyatasa Byan; Hadi Setiyawan; Jaka Septian Kustanto; Edi Kurniawan; Teguh Pribadi (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2026)
This study aims to design and develop an Internet of Things (IoT)-based electrical energy source monitoring system for ships to support the utilization of renewable energy, particularly Wind Power Generation (WPG). The background of this research is the continued use of manual monitoring systems, which are less effective, prone to recording errors, and unable to provide real-time data monitoring. The developed system utilizes a ZMPT101B voltage sensor, an ACS712 current sensor, an ESP32 microcontroller, a 20×4 I2C LCD, and the Node-RED platform for data visualization and storage. This study employs a quantitative experimental method, including hardware design, software development, and static and dynamic testing. Testing was conducted at two locations, namely the Merchant Marine Polytechnic of Surabaya and Kenjeran Beach, Surabaya, for 8 hours. The results show that the system performed successfully, displaying real-time data through both the LCD and Node-RED dashboard while also enabling automatic data logging without data loss. The ACS712 sensor exhibited an error range of 2.38%–7.14%, while the ZMPT101B sensor showed an average error of approximately 0.8%. Based on these results, the developed IoT-based monitoring system is considered feasible for shipboard electrical monitoring and has the potential to improve operational efficiency in electrical monitoring activities.